Kinetic Modelling Of The Formation Of Titanium Hydride From The Reaction Between Magnesium Hydride And Titanium Tetrachloride Using Matlab - Zainordin, Atif Sadaqi (Universiti Sains Malaysia, 2017)
The reaction between Magnesium Hydride (